ChIP analysis of the histone modifications at the D4Z4 repeats in facioscapulohumeral muscular dystrophy (FSHD) - Vafadar-Isfahani, Natasha (2010)
Genomic DNA must exist in a particular chromatin configuration and modification of this structure is essential for the correct control of gene expression. There are several human genetic disorders that are caused by misregulation of epigenetic gene control. Facioscapulohumeral muscular dystrophy (FSHD) is a disease that may be caused by alterations in chromatin structure. FSHD is the third most common form of muscular dystrophy. The majority of FSHD cases show contraction of the D4Z4 repeats on the 4q35 chromosome (FSHD1). However, a small number of FSHD cases show no contraction at this region (FSHD2), but share epigenetic changes at the D4Z4 region with the FSHD1 patients. In 2009, Zeng et al. reported a specific loss of H3K9me3 histone modification at the D4Z4 repeats in FSHD patients. The main focus of this study was to verify the published data by Zeng et al (2009) and further investigate the histone modification changes at the D4Z4 array. Chromatin immunoprecipitation (ChIP) coupled with real-time quantitative PCR (qPCR) was employed to investigate the histone modifications within the D4Z4 array. The results obtained were in agreement with the previously published data on the reduction of H3K9me3 histone modification at the D4Z4 repeats in FSHD patients. However, contradictory to the previous data, the reduction of this histone modification was also observed on other genomic regions. A global reduction of H3K27me3 was also observed in FSHD patients.